Investigating The Impact Of Brand Image Towards Customer Loyalty: A Case Study Of Brand Xy - Abryanto, Rano Abryanto, (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2025)
Each brand employs distinct strategies to engage customers and encourage product purchases. The objective of this research is to ascertain the influence of brand image on customer loyalty. The dimensions utilized in this research are: Brand Awareness, Product Quality, and Customer Satisfaction. The data was gathered from 167 respondents aged 18 to 40, residing in the Jabodetabek region. The results demonstrated that brand image influenced consumer loyalty by 77.7%. Moreover, brand image, perceived quality, and perception significantly influence customer loyalty. Brand Recall and Product Design have the least substantial impact on customer loyalty. This study has identified the essential elements for the company to enhance its advertising and provides recommendations for future writers.